Implementation plasma chemical etching in submicron technology wsi structure - Новосядлий, Степан Петрович; Мельник, Любомир Васильович; Новосядлий, Святослав Володимирович (Eastern-European Journal of Enterprise Technologies, 2015)
With the development of a range of sub–micron devices elements inthralnyh large schemes, a number of problems, which either did not exist in the development of technology of integrated circuits with minimum dimensions of elements, or they did not identify significant. Thus reducing the geometric dimensions topology structures LSI, accompanied by a decrease in the thickness of the functional layers of multilayer structures used to represent a theoretical requirements for selectivity and anisotropy etching layers introduced defects and radiation damage to the surface of the processed wafers of silicon or gallium arsenide structures of integrated circuits. To determine the optimal technological regimes digestion ranged basic operating parameters of the process – the composition and working gas pressure, bias voltage and holder, holder distance to the source plasma. This article reveals the same perspective and alternative use of submicron technology of plasma chemical etching.